Reconstruction of Thumb Polydactily: A Case Report - Budiman, Budiman; Utami, Gladya; Nazwan Sani, T. Fadli (Lingkar Studi Bedah Plastik Foundation, 2019)
Background: Polydactyly is the most common hand congenital abnormality found, next after syndactyly. The presence of these extra fingers is not merely duplication but is accompanied by abnormal hypoplastic structures, abnormal joints, tendon anomalies, and anomly of the insertion of ligaments. There are many tehniques proposed to reconstruct polydactyly, from simple excision of bones, ligaments, and tendons to complex reconstructions. We report a case of polydactily, the patient had bone exicision of the duplicates when the patient was four-month-old, but that extra metacarpal with no phalanges resulted in a greater space of finger 1 and 2. Patient and Method: A 21-year-old woman complaining of difficulty in grasping because the space between first and second fingers is too far away, and the extra metacarpal bone is protruding that causes snagging and stumbling on other objects. She had a history of surgical removal of polydactyl when she was 4-month-old. The patient has a limitation in hand activities. Result: Six months after surgery, the patient was satisfied with the results. The fingers has better mobility, good appearance. No more prominent bone, and neuropathic problems, or other disorders were found. Conclusion: Polydactyly is a common congenital hand occurrence. Understanding the anatomy to guide the reconstructive actions is important. It is not only about which digit would be preserved, but we have to concern about what our patient need, improving the quality, patient's hand function, and the aesthetic aspect.